Estudio de degradación de descargadores de óxido de zinc tipo distribución (2012)
A pilot study is carried out to determine the variations in the electrical characteristics of the surge arrester of ZnO due to the phenomenon of degradation. The electric variables considered are the coefficient of nonlinearity and the dissipated power by the surge arrester. There are other methods to determine the operational status of an unloader as is the study of the resistive component of the leakage current in AC, not be taken into account in this work. Laboratory tests were conducted by accelerating the degradation process through implementation of energy to the samples and simulating an degradation effect by applying heat. The results show variations in the electric variables that can be used to establish a program for reviewing the operational status of the surge arrester in electric networks.